Taxonomical revision of Cambeva stawiarski (Miranda Ribeiro, 1968) (Siluriformes, Trichomycteridae) with the description of a new species from the Rio Iguaçu basin, Paraná State, Brazil. - Reis, Renan Borges dos (2021)
The objective was to redescribe Cambeva stawiarski, using internal morphological data, external morphology, morphometry and meristic data, through the revision of the type-material and material deposited in fish collections. In this process, we have also added comments on the possible Cambeva stawiarski type-locality and described a new species of Cambeva, endemic to the Rio Iguaçu basin, Brazil. Cambeva stawiarski and the new species are diagnosed by the number of procurrent caudal-fin rays dorsally and ventrally; number of vertebrae; number of pectoral-fin rays; number of branchiostegal rays; small notch on the distal margin of the caudal-fin; head length; caudal peduncle depth; and the colouration pattern of the body. In addition, the species are compared with other possibly related species and the synapomorphic characters of these groups of species are discussed. With confirmation of the endemism of Cambeva stawiaski and the description of a new species of Cambeva for the Rio Iguaçu basin, we confirm important biogeographic patterns on the endemism of this hydrographic basin and in the use of osteological data in the description of Cambeva species.